Development of bioorganic containing endophytic fungus Phlebia GanoEF3 for oil palm growth and control of basal stem rot disease - Anuar, Erma Nadia (2014)
The oil palm, Elaeis guineensis, is the highest oil-yielding among the oil-producing crops. Like any other crops, oil palm is prone to infection by a number of diseases, and one of the most serious diseases is basal stem rot (BSR). The disease is caused by species of Ganoderma. Recent control measure to control Ganoderma associated with BSR is now focused on the use of biological control agents such as endophytic fungi. Therefore, the objectives of this study were; 1) to develop powder formulations of endophytic fungus Phlebia GanoEF3 by incorporating organic and inorganic fertilizer as a carrier, 2) to study the potential of bioorganic containing endophytic fungus Phlebia GanoEF3 as a biological fertilizer for enhancing the growth of oil palm seedlings and 3) to study the capability of bioorganic containing endophytic fungus Phlebia GanoEF3 to suppress BSR disease in oil palm seedling. An initiative to isolate endophytic microorganisms from trunk and root tissues of oil palms by the Malaysian Palm Oil Board (MPOB) has found promising fungi, including Hendersonia GanoEF, Amphinema GanoEF2 and Phlebia GanoEF3. Two types of organic fertilizers; Empty Fruit Bunches (EFB) powder and Real Strong Bioorganic Fertilizer (RSBF) were incorporated into the formulation to develop biofertilizers containing endophytic Phlebia GanoEF3. Five ratios of fertilizer (EFB/RSBF) to vermiculite containing endophytic Phlebia GanoEF3 (10:50, 20:40, 30:30, 40:20 and 50:10) for each formulation were prepared and in vitro study and the shelf life of viable cell of Phlebia GanoEF3 in the powder formulations during storage were determined. It was found that the ratio of 30 g of EFB powder to 30 g of vermiculite containing endophytic Phlebia GanoEF3 (30:30 g) and 10 g of RSBF to 50 g of vermiculite containing endophytic Phlebia GanoEF3 (10:50 g) recorded the highest number of fungal colony population among other ratios, where product with EFB was with 51% percentage inhibition of radial growth (PIRG) against G. boninense, a month after storage of the product and 15% at the end. Meanwhile, 10 g of RSBF to 50 g of vermiculite containing endophytic Phlebia GanoEF3 (10:50 g) recorded 56% PIRG value after a month of product storage, and 17% after eight months of storage. Plant growth result showed that Treatment 3 seedlings (10 g of RSBF to 50 g of vermiculite containing endophytic Phlebia GanoEF3) gave the highest result in number of frond (18.23), frond length (73.56 cm), plant height (107.5 cm), number of leaflets (38.33), stem diameter (60.06 mm) and leaf area index (4355.92 cm2), followed by Treatment 2 seedlings (30 g of EFB powder to 30 g of Phlebia GanoEF3) which gave the highest result for total chlorophyll content (70.43 μg/L) and total biomass (105.95 cm), and control treatment (Treatment 1). Pathological parameter analysis showed that ratio of 30 g of EFB powder to 30 g of vermiculite containing endophytic Phlebia GanoEF3 (Treatment 3) and 10 g of RSBF to 50 g of vermiculite containing endophytic Phlebia GanoEF3 (Treatment 4) also have good potential in inhibiting the growth of G. boninense in order to suppress basal stem rot disease (BSR) on oil palm seedlings. It was found that the percentage of disease incidence (DI) for T3 and T4 seedlings were only at 50% and 40%, respectively, compared to the control seedlings (T2) which suffered a total of 100% diseased seedlings. The area under the disease progress curve (AUDPC) for T3 (130 units2) and T4 (140 units2), disease reduction (DR) for T3 (63.89%) and T4 (61.11%), disease severity of foliar index (DSFI) for T3 (35%) and T4 (20%), disease severity of bole index (DSBI) for T3 (40%) and T4 (32.5%), disease severity of root index (DSRI) for T3 (50%) and T4 (41%) and dead seedlings for T3 (30%) and T4 (20%), all showed reduction in values compared to control seedlings (T2). Based on all the results, it was found that Bioorganic containing Phlebia GanoEF3; Bioorganic EFB Phlebia GanoEF3 and Bioorganic RSBF Phlebia GanoEF3 were effective in promoting oil palm seedlings growth and suitable as an effective biological control agent for controlling BSR disease.